Implementation of infrared therapy at posbindu Padukuhan Gadingan - Iswanto Suwarno; Yoga Ihsan Rianto; Ramadhani Prayoga; Nia Maharani Raharja; Robbi Rahim; Victor Jiménez-Díaz-Benito; Belinda Lai; Ursula Hadimeri (Peneliti Teknologi Teknik Indonesia, 2023)
Elderly (elderly) is very vulnerable to health. The elderly have physical problems and need more care. The number of elderly people continues to increase from year to year. Along with the increasing number of elderly people, the government has formulated various policies for elderly health services that aim to improve the health status and quality of health for the elderly in order to achieve a happy and useful old age in family life, society in accordance with their existence. Supplementary Feeding (PMT) is an activity of providing food to toddlers in the form of food that is safe, of good quality, and contains nutritional value according to the needs of children. POSBINDU and also PMT are routine activities held at Padukuhan Gadingan every month to monitor the health of the elderly and help support nutrition in children. The purpose of this community service is to introduce infrared light therapy devices and invite the elderly to try therapy with these tools, and also help provide supplementary food (PMT) for toddlers in Padukuhan Gadingan. The methods used include surveys, the preparation stage, and finally the activity implementation stage. The targets of this infrared ray therapy activity are residents of Gadingan Padukuhan in general, as well as the elderly in particular. The target of PMT activities are toddlers in Padukuhan Gadingan. Community service activities by providing infrared light therapy have a positive impact on residents, especially for the elderly. This can be seen from the testimonies of residents who have tried therapy, they say that the pain they felt before was reduced after they had therapy.